2016
DOI: 10.1186/s41065-015-0005-6
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary phylogeny of the South African Lentulidae

Abstract: BackgroundThe grasshopper family Lentulidae is endemic to eastern and southern Africa, with its center of diversity situated in South Africa, the highest diversity being found in the Cape Floristic Region, which is one of the global biodiversity hotspots. The family consists of 35 genera sorted in two subfamilies. This study provides first insights into the phylogeny of Lentulidae. Two mitochondrial genes (12S and NDS) were sequenced and the phylogeny was inferred through Maximum Likelihood and Bayesian Infere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…The present study adds to a growing list of clinical and epigenetic evidence supporting the role of perinatal environment in modulation of DNA methylation in newborn tissues [42], suggesting that DNA methylation linked to the pregnant women nutritional status may have specific target genes that may be linked to the phenotype of risk for obesity later in life. SNPs of GNPDA2 , PGC1α , and LEPR genes contribute to an increased risk of obesity development in Mexican population [28,30–32], and some evidence strongly suggests that obesity-associated polymorphisms are linked with proximal gene regulation, such as enhancers and promoter regions that are differential methylated [43]. According to our knowledge, this study is the first one examining DNA methylation status in a single locus of GNPDA2 promoter, and the third one that evaluated the PGC1α promoter methylation status in umbilical cord [44,45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study adds to a growing list of clinical and epigenetic evidence supporting the role of perinatal environment in modulation of DNA methylation in newborn tissues [42], suggesting that DNA methylation linked to the pregnant women nutritional status may have specific target genes that may be linked to the phenotype of risk for obesity later in life. SNPs of GNPDA2 , PGC1α , and LEPR genes contribute to an increased risk of obesity development in Mexican population [28,30–32], and some evidence strongly suggests that obesity-associated polymorphisms are linked with proximal gene regulation, such as enhancers and promoter regions that are differential methylated [43]. According to our knowledge, this study is the first one examining DNA methylation status in a single locus of GNPDA2 promoter, and the third one that evaluated the PGC1α promoter methylation status in umbilical cord [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…GWAS studies have identified common genetic variants associated with BMI of children and adults among European, Chinese, Japanese and Mexican populations [16,2628], suggesting that there is a genetic risk for obesity [29]. Specific variants of GNPDA2 , PGC1α and LEPR genes have shown a strong association with Mexican population’s BMI, increasing the risk of obesity [28,30–32], although the control mechanisms of obesogenic genes expression during early development are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the southeastern Cape is proposed as both a cradle and a refuge for Epirinus. Climatic refugia in southern Africa have been previously reported in mammals (Lawes et al, 2007;Maswanganye et al, 2017), reptiles (Tolley, Chase, & Forest, 2008;Barlow et al, 2013;Nielsen et al, 2018) and insects (Price, Barker, & Villet, 2007;Sole et al, 2013;Switala, Sole, & Scholtz, 2014;Matenaar, Bröder, & Hochkirch, 2016;Strümpher et al, 2016;Daniel et al, 2020b;Hemp et al, 2020), supporting the idea of climatically driven speciation of…”
Section: Speciation Processes In Epirinusmentioning
confidence: 64%
“…Summary of findings of grasshopper use of different patches in the agro-natural landscape of Cape Floristic Region (CFR): arrows in the graph point towards inclusion; HMG -high mobility, generalist feeders, LMG -low mobility, specialist feeders Most Lentulidae, Hemiacridinae, Eyprepocnemidinae, Pyrgomorphidae and some Oediponidae (mostly apterous to brachypterous, localised/endemic, forb to mixed feeders with limited to medium mobility) species use only one or few habitat patches in heterogeneous landscapes. This is because most species in these groups, especially Hemiacrididae (Spearman, 2013) and Lentulidae species (except for a few, such as E. ottei), are only associated with fynbos with slight changes in densities throughout the seasons (Matenaar et al, 2014(Matenaar et al, , 2018. Under optimum environmental conditions these species will locate the best possible ha-bitats in the fynbos or any other patch on the landscape within a particular period of the year (Loreau et al, 2013).…”
Section: Discussionmentioning
confidence: 99%